Membangun Keprofesian Guru Melalui Manajemen Pemberdayaan Kelompok Kerja Guru (KKG) Yang Efektif Dan Berkelanjutan - Miftahusyai'an, Mohammad; Mulyoto, Galih Puji; Lestantyo, Prayudi; Munir, Misbah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The purpose of this study is first, to find the formulation of KKG empowerment strategy in the development of sustainable professionalism for Islamic Religious Education (PAI) Teachers and to find the impact and obstacles of effective empowerment of Teacher Working Groups (KKG) in the development of sustainable professionalism. This study uses the Participatory Action Research (PAR) research method. The subjects of the study include the administrators of KKG PAI Teachers. Data collection techniques use documentation, interviews and observations. Data analysis techniques use interactive analysis techniques (interactive analysis model). The results of the study indicate that in formulating a KKG empowerment strategy in the development of sustainable professionalism for PAI Teachers, it is carried out through PAR steps using the term KUPAR (to Know, to Understand, to Plan, to Action and to Reflection). The use of PAR steps in empowering KKG is able to compile programs in the development of effective sustainable professionalism for PAI Teachers. The follow-up to the results of this study is the creation of a PKB program for PAI Teachers consisting of self-development, scientific publications and innovative works implemented in several ways. This can be a reference for related parties in implementing the empowerment model through KKG for the development of sustainable professionalism for Islamic Religious Education Teachers.